NILAI TUKAR DAN KEDAULATAN RUPIAH - Zainal Arifin H. Masri; Syamsul Hadi (Universitas Indraprasta PGRI, 2016)
Exchange rate is the price of a currency of a country that is measured or expressed in other currencies. Exchange rate or the exchange rate is a key for a country to trade with the outside world. Payment system performed well in the country and abroad would not want to be tied to the exchange rate or the exchange rate. Exchange rate system consists of several types, namely: Fixed Exchange Rate (Fixed Exchange Rate), a Floating Exchange Rate Controlled (Managed Floating Exchange Rate), Free Floating Exchange Rates (Free Floating Rate). UU No. 7/2011 on Currency has set the obligation to use rupiah on each transaction in Indonesia. Yet it is about 4 years passed, these rules can not run optimally. There are still some communities, especially in border areas, the use of foreign currency in the transaction. If allowed, then the public will continue to trade with foreign exchange and the impact is the weakening of the rupiah. Negative impact on our economy. Use of the rupiah currency as a means of transaction in the country is also to keep the rupiah sovereignty sovereignty of the Homeland at the same time. Rupiah is also a legal tender so it must be used in economic activities in the territory of the Republic of Indonesia in order to realize social welfare for all the people of Indonesia, including in the forefront of Indonesia. Keywords : exchange rate, a fixed exchange rate, sovereignty rupiah.